2010
DOI: 10.1519/jsc.0b013e3181cc26e0
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of An Ascending Squat Protocol on Performance During Horizontal Plyometric Jumps

Abstract: The purpose of the present investigation was to examine the effects of a strength-power potentiation complex that involved performing a horizontal plyometric activity 5 minutes after the completion of an ascending back squat protocol. Twelve men who could back squat a minimum of 1.5 time body mass participated in a familiarization session and 2 randomly assigned testing sessions each separated by approximately 1 week. In the control session, the subject rested for 5 minutes and then performed the horizontal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 27 publications
(81 reference statements)
5
30
1
1
Order By: Relevance
“…Careful inspection of the literature suggests that athletes who squat a minimum of 23 body mass can express higher power outputs than their weaker counter parts (1.7 or 1.43x body mass) in vertical (6,71) and horizontal jumping activities (64). Additionally, Wisløff et al (86) suggests that soccer players who can squat .2.03 body mass are significantly faster and able to jump higher than those who squat ,2.03 body mass.…”
Section: Maximal Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful inspection of the literature suggests that athletes who squat a minimum of 23 body mass can express higher power outputs than their weaker counter parts (1.7 or 1.43x body mass) in vertical (6,71) and horizontal jumping activities (64). Additionally, Wisløff et al (86) suggests that soccer players who can squat .2.03 body mass are significantly faster and able to jump higher than those who squat ,2.03 body mass.…”
Section: Maximal Strengthmentioning
confidence: 99%
“…Additionally, Wisløff et al (86) suggests that soccer players who can squat .2.03 body mass are significantly faster and able to jump higher than those who squat ,2.03 body mass. Recent work by Keiner et al (43) reports that youth (64) and ballistic exercises such as jump squats (17). Overall, it is apparent that a minimum back squat of 2.03 body mass is at best a minimum strength requirement before specialized training for the optimization of lowerbody power development should occur.…”
Section: Maximal Strengthmentioning
confidence: 99%
“…Le Myotest, par exemple, a été utilisé chez des joueuses de handball non professionnelles afin d'objectiver l'efficacité de deux courtes séances de musculation sur la puissance des membres inférieurs, la puissance des bras et la détente verticale (Jidovtseff et al, 2014). Plusieurs études ont utilisé un accéléromètre afin d'explorer la potentiation musculaire lors du travail par contraste de charge en développé couché (Liossis et al, 2013, Cabrera et al, 2009Morio et al, 2011 ;Ruben et al, 2010). Un accéléromètre uniaxial a été utilisé afin d'étudier l'évolution de la puissance des membres inférieurs (presse) et la puissance des bras (développé couché) en fonction de l'âge .…”
Section: Applications Pour La Détermination D'un « Profil Musculaire unclassified
“…PAP refers to the phenomenon by which the acute contractile ability of a muscle is enhanced in response to a conditioning stimulus such as a heavy resistance exercise (HRE). From a practical standpoint, PAP has been suggested to exploit the enhancement of athletic performance 7 , however, the responses to PAP seem to be highly individualized based on responders vs non-re-sponders 8,9 . Literature has suggested that with several players positively responding to PAP protocols, others players may not significantly improve their performance with this method 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…From a practical standpoint, PAP has been suggested to exploit the enhancement of athletic performance 7 , however, the responses to PAP seem to be highly individualized based on responders vs non-re-sponders 8,9 . Literature has suggested that with several players positively responding to PAP protocols, others players may not significantly improve their performance with this method 8,9 . The efficacy by which a conditioning activity can stimulate PAP mechanisms and acutely enhance muscular performance ultimately depends on the balance between PAP and fatigue which may be affected by numerous factors including the rest interval between PAP and the effort required 10 , training experience 11 , intensity 5 and the volume of PAP 12 .…”
Section: Introductionmentioning
confidence: 99%